Sustainability in a Water Bottle: CSR and Buying Intention of Le Minerale - Tania Monica Potu; Janice Carysa Siahaya; Priskilla E.E. Napitupulu (Universitas Pelita Harapan, 2025)
This study investigates the influence of Corporate Social Responsibility (CSR) on competitive advantage (CA) and buying intention (BI) in the bottled water industry, focusing on Le Minerale in Surabaya, Indonesia. CSR is examined across four dimensions: legal and ethical responsibility, philanthropic and community services, respect for environment, and respect for customers. Using a quantitative approach with purposive sampling, 100 valid responses were collected from consumers-dominantly aged 17-25 who worked in private companies who purchased Le Minerale and are aware of its CSR activities. Data was analyzed through validity, reliability, normality, and regression tests using SPSS. The results reveal that CSR has a significant and positive effect on competitive advantage, explaining 74.5% of its variance. Furthermore, competitive advantage significantly influences buying intention, accounting for 52.3% of its variance. These findings suggest that CSR initiatives not only strengthen Le Minerale’s market positioning but also foster consumer trust, which eventually enhances buying intention. However, practical factors such as price and accessibility also shape purchasing decisions. The study highlights CSR as a strategic driver of sustainable competitiveness in a low-involvement market like bottled water.